Phase formation processes and synthesis of solid solutions in Ca-R-Nb-M-O systems - A. A. Levina; N. O. Tadevosyan; S. A. Petrova; E. S. Buyanova; M. V. Morozova (Chimica Techno Acta)
During the study of the phase formation process in Ca-R-Nb-M-O systems (R=La, Bi, M=Mo, W), an attempt was made to obtain single-phase compounds of CaRNbMO8 composition by the standard ceramic technique. In addition, samples based on LaNbO4, CaWO4, BiNbO4 were also synthesized by the standard ceramic technique. The phase composition of the samples was studied by XRD analysis. The electrical conductivity of the obtained solid solutions and potential composite materials was investigated by impedance spectroscopy.